Formation and Characterization of Mycelium–Potato Protein Hybrid Materials for Application in Meat Analogs or Substitutes - Ramdattu Santhapur; Disha Jayakumar; David Julian McClements (Foods)
There is increasing interest in the development of meat analogs due to growing concerns about the environmental, ethical, and health impacts of livestock production and consumption. Among non-meat protein sources, mycoproteins derived from fungal fermentation are emerging as promising meat alternatives because of their natural fibrous structure, high nutritional content, and low environmental impact. However, their poor gelling properties limit their application in creating meat analogs. This study investigated the potential of creating meat analogs by combining mycoprotein (MCP), a mycelium-based protein, with potato protein (PP), a plant-based protein, to create hybrid products with meat-like structures and textures. The PP-MCP composites were evaluated for their physicochemical, rheological, textural, and microstructural properties using electrophoresis, differential scanning calorimetry, dynamic shear rheology, texture profile analysis, confocal fluorescence microscopy, and scanning electron microscopy analyses. The PP-MCP hybrid gels were stronger and had more fibrous structures than simple PP gels, which was mainly attributed to the presence of hyphae fibers in mycelia. Dynamic shear rheology showed that the PP-MCP hybrids formed irreversible heat-set gels with a setting temperature of around 70 °C during heating, which was attributed to the unfolding and aggregation of the potato proteins. Confocal and electron microscopy analyses showed that the hybrid gels contained a network of mycelia fibers embedded within a potato protein matrix. The hardness of the PP-MCP composites could be increased by raising the potato protein content. These findings suggest that PP-MCP composites may be useful for the development of meat analogs with more meat-like structures and textures.